(untitled) (KULT_online, 2020)
Paolozzi and Wittgenstein. The Artist and the Philosopher, published in summer 2019, is dedicated to the significance of Ludwig Wittgenstein for the work of the British Pop Art artist Eduardo Paolozzi. So far, Paolozzi’s intensive and fundamental examination of the work and life of the Viennese philosopher is still little present in the reflection on the relationship between philosophy and art. To change this is the firm intention of the book’s editors, Diego Mantoan and Luigi Perissinotto. And even if the quality of the contributions fluctuates, they do manage to make Paolozzi visible as a genuine artistic interpreter of Wittgenstein and his art the angle under which the philosopher, too, appears in a different light.